ANALISA EFISIENSI ISENTROPIK PADA ASH REMOVAL COMPRESSOR DENGAN SOFTWARE COMPUTER AIDED THERMODYNAMICS TABLE 3 - Ramadhan, Muhammad Nizar; Roby, Muhammad (Machine : Jurnal Teknik Mesin, 2025)
Steam Power Plant (PLTU) is a plant that relies on kinetic energy from steam to produce electrical energy. One of the components used to run the system in PLTU is an air compressor. In Pulang Pisau Steam Steam Power Plant, Air Screw Compressor is used to meet the needs of compressed air in air instruments and ash removal. This study aims to analyze the isentropic efficiency of ash removal screw compressors 2 and 3 at Pulang Pisau Steam Power Plant by comparing the isentropic value of factory specifications with the isentropic value of actual conditions using Computer Aided Thermodynamics Table 3 (CATT3) software. The method carried out in this study is divided into two, namely taking actual data in the field and calculating data using CATT3 software. The results showed that the average isentropic efficiency value of ash removal compressor 2 is 84% and ash removal compressor 3 is 83% with a range of values of 77% - 89%. From these results, it can be concluded that ash removal compressors 2 and 3 at the Pulang Pisau Steam Power Plant are still working properly.